Pengaruh Persepsi Pelayanan, Manfaat dan Lokasi terhadap Keputusan Mustahik Memilih Rumah Sehat BAZNAS di Indonesia: Pengetahuan Sebagai Variabel Moderasi - Maulana Abidin; Slamet Haryono (Universitas Batanghari Jambi, 2022)
This study aims to determine how the effect of service perception, benefits and location on mustahik's decision to choose a BAZNAS Healthy Home in Indonesia, for research methods using quantitative methods with field research and Multiple Linear Regression analysis tools, the source of data in this study is BAZNAS Healthy House mustahik. in Indonesia, as well as a tool to determine respondents using the Slovin formula as many as 100 respondents. The results of this study with the Simultaneous test have a positive impact of 46% on the decision to choose a BAZNAS Healthy Home in Indonesia which is influenced by other exogenous variables that are not used in this study, then knowledge of service perception on mustahik's decision to choose a BAZNAS Healthy Home in Indonesia with a Path Coefficient Value is 0.097 and P-Values 0.160 means 0.160 > 0.05 means Rejected, knowledge moderates the perception of benefits on the mustahik decision to choose a BAZNAS Healthy Home in Indonesia with a Path Coefficient Value of 0.330 and a P-Values value of 0.001, it means 0.001 < 0.05, accepted, and knowledge of location perception of mustahik's decision to choose a BAZNAS Healthy Home in Indonesia with a Path Coefficient Value of -0.229 and a P-Values value of 0.008, meaning 0.008 < 0.05 accepted.